BRANDING DESA WISATA DENGAN KONSEP GREEN ECONOMY - Muhammad Arfa (JURNAL IMAJINASI, 2024)
This study focuses on the sustainability of Batu Kumbung Tourist Village, which has significant potential to develop the concept of a green economy as an effort to enhance environmental sustainability and the local economy. This concept involves not only the wise use of natural resources but also promotes environmentally friendly practices in agriculture, tourism, and micro, small, and medium enterprises (UMKM). Organic farming and wise waste management are among the green economy initiatives. The aim of this thesis is to provide insights for the development of a local economy, particularly sustainable tourist villages, that have a positive impact on the environment in the future. The research method used is descriptive qualitative, with data collection techniques conducted through triangulation (combination). The research findings show that green economy policies have already been implemented in Batu Kumbung tourist village by adopting the development of a green economy concept. Zero waste activities become a strategic effort to maintain the environmental sustainability of Batu Kumbung tourist area